Characteristics of flow field and pressure fluctuation in complex turbulent flow in the third elbow of a triple elbow piping with small curvature radius in three-dimensional layout. (11th May 2016) - Ebara, Shinji; Takamura, Hiroyuki; Hashizume, Hidetoshi; Yamano, Hidemasa
Abstract: In this study, a flow visualization and pressure measurement were conducted by using an experimental setup including test sections of 1/7-scale models of the cold-leg piping of Japan sodium-cooled reactor with high Reynolds number region up to about one million. Regarding the flow field, flow separation appeared in the intrados of the third elbow. However, the separation region was smaller than that observed in the first elbow in the direction normal to the mean flow and was larger in the streamwise direction. This can be considered because of the swirling flow vgenerated downstream of the second elbow which flowed into the third elbow with a little reduction. From the pressure fluctuation test, it was found that prominent frequencies of the pressure fluctuation appeared at about 0.4 in Strouhal number, which corresponds to a nondimensional frequency, in the region from 0 D to 0.4 D downstream of the elbow outlet, where D is the diameter of the piping. And weak peaks of about 0.7 in Strouhal number were observed in the region far 0.75 D downstream of the outlet. The peak values were about 1/4 of those in the first elbow. This means that the excitation source in the third elbow becomes smaller than that in the first elbow for the fully developed inflow case. Highlights: The flow field and pressure fluctuations in a triple elbow piping are measured. A separated region in the 3rd elbow is thinner and longer than that in the 1st elbow. Periodicity of shed vortices from the separated region in the 3rd elbow is weak. Intensity of pressure fluctuation downstream of the 3rd elbow is low.